Development of pseudo-subarachnoid hemorrhage secondary to hypoxic-ischemic injury due to bleeding pulmonary artery-venous malformation - Md Noh, Mohamad Syafeeq Faeez; Abdul Rashid, Anna Misya'il (BioMed Central, 2018)
Background: The computed tomography (CT) finding of a pseudo-subarachnoid hemorrhage (SAH) may lead the treating physician into a diagnostic dilemma. We present a case of a pseudo-SAH in a patient with post-resuscitative encephalopathy, secondary to a newly diagnosed bleeding pulmonary arterio-venous malformation (AVM). Case presentation: A 19-year-old female presented acutely with massive hemoptysis. Cardiopulmonary resuscitation (CPR) followed, and the patient was subsequently intubated for airway protection with intensive care unit (ICU) admission. Urgent CT angiography of the thorax showed a bleeding pulmonary AVM, with evidence of hemothorax. Non-contrasted cranial CT initially revealed cerebral edema. Day 3 post admission, repeat cranial CT showed worsening cerebral edema, with evidence of pseudo-SAH. Patient passed away the next day. Conclusions: Pseudo-SAH, if present, carries a poor prognosis. It should be recognized as a potential CT finding in patients with severe cerebral edema, due to various causes. The diagnosis is vital, to avoid wrongful treatment institution, as well as determination of cause of death.